Norswertianolin Promotes Cystathionine γ-Lyase Activity and Attenuates Renal Ischemia/Reperfusion Injury and Hypertension - Niu, Yaping; Du, Congkuo; Cui, Changting; Zhang, Haizeng; Deng, Yue; Cai, Jun; Chen, Zhenzhen; Geng, Bin (Frontiers in Pharmacology, 2021)
Cystathionine gamma-lyase (CSE)/Hydrogen sulfide (H2S) plays a protective role in cardiovascular diseases including hypertension and ischemia reperfusion (I/R) injury. This study aimed to screen natural small molecule compounds that activates CSE activity then evaluates its effect(s) on kidney I/R injury and hypertension. Applying computer molecular docking technology, we screened the natural small molecule compound-norswertianolin (NW) specific binding to CSE. Using the microscale thermophoresis technology, we confirmed that Leu68 site was the essential hydrogen bond site of NW binding to CSE. NW supplementation significantly increased CSE expression, and its activity for H2S generation both in vivo and in vitro. In the model of acute and long-term kidney I/R injury, NW pretreatment dramatically attenuated kidney damage, association with decreasing blood urea nitrogen (BUN), serum creatinine (Cr) level, reactive oxygen species (ROS) production and cleaved caspase 3 expression. In spontaneous hypertensive rats (SHR), NW treatment also lowered blood pressure, media/lumen ratio of femoral artery and mRNA level of inflammatory cytokines. In conclusion, NW acts as a novel small molecular chemical compound CSE agonist, direct binding to CSE, heightening CSE generation-H2S activity, then alleviating kidney I/R injury and hypertension. NW has a potential therapeutic merit for cardiovascular diseases.